An approach to prepare lexicons of Assamese text for unit selection concatenation TTS (International Journal of Emerging Trends in Science and Technology, 2017)
Text To Speech synthesizer plays a very important role in modern day Information Technology.Communication technology can be enhanced by speech technology to a greater extent. There are a numberof steps in natural language processing phase of a Text to speech synthesizer. In this paper the approach tomake a TTS for Indian language is shown by taking Assamese as an example. First explanation is how to getlexicons of the language then an idea of using DONLabel tool is shown. To build a speech synthesizer forany language, researcher should acquire adequate knowledge about the phonetic and acoustic characteristicof that language. In this research paper important features of Indian languages, the proposed block diagramfor synthesis process, preparation of lexicons from the written text for Assamese language is explainedwith snapshots.